2016
DOI: 10.1634/theoncologist.2015-0440
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy for Muscle-Invasive Bladder Cancer: A Systematic Review and Two-Step Meta-Analysis

Abstract: Background. Platinum-based neoadjuvant chemotherapy has been shown to improve survival outcomes in muscle-invasive bladder cancer patients.Weperformed a systematic review and meta-analysis to provide updated results of previous findings. We also summarized published data to compare clinical outcomes of methotrexate, vinblastine, doxorubicin, and cisplatin (MVAC) versus gemcitabine and cisplatin/carboplatin (GC) in the neoadjuvant setting. Methods. A meta-analysis of 15 randomized clinical trials was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
257
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(268 citation statements)
references
References 43 publications
5
257
0
6
Order By: Relevance
“…In retrospective analyses, pCR rates ranged from 19 to 31% with MVAC [8,13,14,22] . The pCR rate of 22.5% seen in our cohort using GC is at the lower end of this spectrum, which is in range with previous studies using GC ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In retrospective analyses, pCR rates ranged from 19 to 31% with MVAC [8,13,14,22] . The pCR rate of 22.5% seen in our cohort using GC is at the lower end of this spectrum, which is in range with previous studies using GC ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent meta-analysis included 13 retrospective studies with 1,067 patients treated with GC and 667 patients treated with MVAC. The results showed a pCR rate of 25.7% with GC compared to 24.3% with MVAC ( p = 0.37) [8] . In addition, a prospective evaluation of GC in the neoadjuvant setting has been reported from 3 small prospective trials including between 20 and 35 patients with a maximum median age of 65 years (online suppl.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…A series of pathogenic factors affect the occurrence of bladder cancer, including aging, smoking and environmental pollution (1). The mortality rate of bladder cancer is increasing, even in childhood (1,2). The pathogenesis of bladder cancer is complex, and involves the activation of oncogenes and the inactivation of tumor suppressor genes.…”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine has been considered to be included in NAC regimens because gemcitabine plus cisplatin has a better safety profile than MVAC [36]. A phase III trial comparing GC and MVAC in patients with transitional cell carcinoma of the urothelium demonstrated that both groups had similar efficacy with respect to response, time-to-progression and OS, whereas GC was associated with less toxicity than MVAC [37].…”
mentioning
confidence: 99%